Pengaruh PPN (Pajak Pertambahan Nilai) terhadap Pendapatan Nasional - Yani, Rindy Endry; Simandalahi, Eliata; Nasution, Armin Rahmansyah (Universitas Batanghari Jambi, 2024)
The purpose of this study is to explore the effect of VAT on national income. This research aims to find out how VAT can affect national income and how national income can be affected by VAT.and how national income can be affected by VAT. Research methodused in this study is a qualitative method. Qualitative methodmethod was chosen because the purpose of this research is to understand how VAT affects national income and how national income is affected by VAT.affects national income and how national income is affected by VAT.by VAT. The research method used in this research is aqualitative method with a document analysis approach. Value-added tax (VAT) is an important instrument in a country's fiscal policy, including Indonesia.in a country's fiscal policy, including Indonesia. Thorough data analysisdata analysis and in-depth discussion show that VAT has a positive and significant influence on national income.positive and significant influence on national income.